Parsis of India continuing at the crossroads - Desai, Armaity S (Armaity Sapur) 1934-; Bharat, Shalini; Lata Narayan; Siva Raju, S 1954- (Los Angeles Sage, 2017)
"First comprehensive analysis of the Parsi community and its demographic decline. 'Where have our people gone?' is a common refrain heard from Parsis. More than a decade ago UNESCO alerted the community of possible extinction. The situation unfortunately has not improved; it continues along the same path. Based on primary data, this four-volume series critically analyses the situation of the ethno-religious Parsi minority of India against the backdrop of its demographic decline. With original scholarly writings and empirical research from multiple sites using mixed method research approach, the series addresses key concerns impacting Parsi demography. Extensive in scope and investigative in analysis, this is the only major socio-psycho-anthropological work in over a decade on the dwindling Parsi community"--Provided by publisher.
Volume 1. The Indian Parsis : themes old and new / volume editors, Shalini Bharat and Armaity S. Desai -- Volume 2. Contemporary Parsis : marriage, family and community / volume author, Shalini Bharat -- Volume 3. The world of Indian Parsi youth : status and perceptions / volume author, Lata Narayan -- Volume 4. The Parsi elderly : to live with dignity / volume author, S. Siva Raju.
Includes bibliographical references and index.
Keywords: Parsees -- India -- Social conditions; Parsees -- India -- Social life and customs; Parsees -- India -- Psychology; Community life -- India; Religious minorities -- India; Demographic transition -- India; India -- Ethnic relations